ANALISIS ERODIBILITAS TANAH DAN HUBUNGANNYA DENGAN PRODUKTIVITAS TANAMAN KOPI DI KECAMATAN WAJAK, KABUPATEN MALANG - Sholikah, Dinna Hadi; Naufal, Raihan; Sigit Wicaksono, Kurniawan; Soemarno, Soemarno (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Coffee plants (Coffea sp.) are among the most popular plantation crops for farmers in Wajak District. However, the soil condition in Wajak District is dominated by sandy soil, which can trigger soil sensitivity to high erosion potential. A mitigation effort for the declining of coffee production in the Wajak District can be made through the estimation of the soil erodibility index. This study aimed to suspect the soil erodibility index and obtain the relationship of soil erodibility index to coffee production on smallholder coffee plantations in Wajak District, Malang Regency. The methods of determining land boundaries with land map units (SPL) were land use, soil type, and slope. The parameters used were soil texture (M), organic matter (a), structure (b), and permeability (c) to determine erodibility, as well as coffee beans for coffee production analysis. Statistical analysis of data was in the form of correlation tests and data regression tests. The results of the data analysis showed that the highest wet weight of coffee fruit was found in SPL 8 with plantation land use, Typic Hapludands soil type and land slope of 8-15%. The wet weight value of coffee fruit at SPL 8 is 2.18 t ha-1 with an erodibility value of 0.37. While the lowest wet weight of coffee beans was found in SPL 2 with moor land use, Andic Eutrudepts soil type and land slope of 8-15%. The average wet weight value of coffee beans at SPL 2 was 0.12 t ha-1 with an erodibility value of 0.26.